1966
DOI: 10.1128/aem.14.1.21-26.1966
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Survey of the Frozen Prepared Foods Industry

Abstract: SURKIEWICZ, BERNARD F. (Food and Drug Administration, Washington, D.C.). Bacteriological survey of the frozen prepared foods industry. I. Frozen cream-type pies. Appl. Microbiol. 14:21-26. 1966.-During Food and Drug Administration inspections of 12 imitation cream pie producers, 453 finished product samples and 350 line samples were collected and analyzed bacteriologically. Sanitary conditions in the plants varied from good to poor and, in general, were reflected in the bacteriological results. The survey reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Plants operating under good sanitary conditions produced crabmeat with average MPN values (geometric) of less than 20 coliform organisms per g, no E. coli, coagulase-positive staphylococci average MPN values (geometric) of less than 30/g 93% of the time, and an average APC (geometric) of less than 100,000/g in 93% of the plants, with 85% of the plants below 50,000/g. Our findings confirm the premise previously established by Surkiewicz et al (6)(7)(8)(9) that insanitary conditions during the processing of food products are reflected in the bacteriological results of the finished product.…”
Section: Phillips and Peelersupporting
confidence: 93%
See 2 more Smart Citations
“…Plants operating under good sanitary conditions produced crabmeat with average MPN values (geometric) of less than 20 coliform organisms per g, no E. coli, coagulase-positive staphylococci average MPN values (geometric) of less than 30/g 93% of the time, and an average APC (geometric) of less than 100,000/g in 93% of the plants, with 85% of the plants below 50,000/g. Our findings confirm the premise previously established by Surkiewicz et al (6)(7)(8)(9) that insanitary conditions during the processing of food products are reflected in the bacteriological results of the finished product.…”
Section: Phillips and Peelersupporting
confidence: 93%
“…1.2 (1) 6.9 (7) 4.5 (6) 4.1 (4) 1.9 (3) 16.0 (9) 10.0 (9) 9.5 (8) 2.1 (3) 7.0 (5) 4.5 (5) 3.8 (4) 6.2 (8) 1.5 (2) 11.0 (8) 36.0 (9) 4.9 (7) 2.3 (4) 24.0 (8) 43.0 (8) 450.0 (5) 620.0 (10) 72.0 (10) 260.0 (10) 1.3 (2) 21.0 (10) 1,070.0 (9) 74.3 (10) 9.5 (8) 7.3 (9) 36,000 50,000 1,000,000 35,000 2,200,000 1,100,000 7,100 150,000 96,000 190,000 22,000 94,000 69,000 1,200,000 120,000 38,000 89,000 360,000 33,000 14,000 140,000 2,100,000 1,200,000 380,000 47,000 360,000 620,000…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review that summarizes these data for chilled and frozen foods was published in 1961 (3). Since then, several other studies have been reported that describe the microbiological quality of various foods (1,(6)(7)(8). These and other data have been used as bases for microbiological standards for a few foods by some states and by the Food and Drug Administration (FDA) (4).…”
mentioning
confidence: 99%
“…A report of the results obtained from this survey, covering the period from March 1958 to June 1959, was issued in 1960 (5). The first of the present series of papers, supplementing the 1960 report, presented the results from a survey of producers of frozen cream-type pies (6). In this paper, the second of the series, we are reporting the phase of the survey which concerns frozen breaded raw shrimp.…”
mentioning
confidence: 96%